ANALISIS MANFAAT MUSYAWARAH GURU MATA PELAJARAN (MGMP) TERHADAP KEMAMPUAN GURU PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN SEKOLAH MENENGAH PERTAMA (SMP) KOTA PEKANBARU - Nurwanuddin, Nurwanuddin; Erlinda, Sri; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abtract: This research is motivated by the start of the implementation of government policies in creating professional and competent teachers. One way to shape the competence of PPKn teachers in Pekanbaru is by having a forum for PPKn Subject Teachers (MGMP) throughout Pekanbaru. This study aims to analyze the role and benefits of the Pekanbaru MGMP in improving Teacher Capability. This type of research is qualitative descriptive which tries to describe the benefits of MGMP on the performance of PPKn teachers. The methods used are surveys, interviews, and lift deployment. The population of this study were all PPKn teachers at the junior high school level in Pekanbaru while the samples taken were teachers who joined the Pekanbaru PPKn MGMP as many as 41 people. Data analysis is done by a combination technique (mix method) that is qualitative data analysis followed by coding and tabulation into percentage tables (Simple Frequency distribution). The results showed that the existence of MGMP was very useful in the performance of PPKn teachers in Pekanbaru City Junior High School. The benefits include 9 main things in accordance with the role of the MGMP, namely; Understanding of curriculum, syllabus and assessment system, making teaching materials, understanding education, implementing computer-based learning programs, developing learning facilities, making learning tools and developing learning media.Key Words: Subject Teacher Consultation, Teacher Ability